2018
DOI: 10.3390/geosciences8110387
|View full text |Cite
|
Sign up to set email alerts
|

Plant Tissue Decay in Long-Term Experiments with Microbial Mats

Abstract: The sequence of decay in fern pinnules was tracked using the species Davallia canariensis. Taphonomic alterations in the sediment–water interface (control tanks) and in subaqueous conditions with microbial mats were compared. The decay sequences were similar in control and mat tanks; in both cases, pinnules preserved the shape throughout the four-month experience. However, the quality and integrity of tissues were greater in mats. In control tanks, in which we detected anoxic and neutral acid conditions, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 83 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…This adsorption was caused by the negative surface charges of bacteria and the biofilm polymer, which resulted in iron encrustations that subsequently inhibited microbial activity and decay. In long‐term experiments with fern leaves (Iniesto et al, 2018), microbial mats entombed the plant material and supported maintenance of tissue integrity as well as mineralization processes. In this sense, the presence of biofilm‐forming bacteria on leaves in a freshwater setting, as predicted by BugBase, would be the first prerequisite for fossilization.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This adsorption was caused by the negative surface charges of bacteria and the biofilm polymer, which resulted in iron encrustations that subsequently inhibited microbial activity and decay. In long‐term experiments with fern leaves (Iniesto et al, 2018), microbial mats entombed the plant material and supported maintenance of tissue integrity as well as mineralization processes. In this sense, the presence of biofilm‐forming bacteria on leaves in a freshwater setting, as predicted by BugBase, would be the first prerequisite for fossilization.…”
Section: Discussionmentioning
confidence: 98%
“…Fossilization of plant material can be induced by different chemical processes, including authigenic preservation, which is dependent on encrustation with minerals. It has been shown that the biofilm‐forming activity of bacteria plays an important role in this process (Dunn et al, 1997; Iniesto et al, 2018). In experiments with dicot leaves that were incubated in mineral solutions containing 10 mM FeCl 3 , only leaves with pre‐formed biofilms were able to adsorb metal ions (Dunn et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have also investigated the impact of biofilm formation (including microbial mats) on preservation and fossilization processes, as well as on the formation of pseudomorphs to replicate soft tissue (e.g. Butler et al, 2015;Darroch et al, 2012;Iniesto et al, 2013Iniesto et al, , 2016Iniesto et al, , 2017Iniesto et al, , 2018Raff et al, 2008Raff et al, , 2013. In the experiments performed by Iniesto et al (2013Iniesto et al ( , 2016Iniesto et al ( , 2017 muscle fibres, bone marrow and skin structures in frogs and fish were preserved after placing the animals on a microbial mat for a duration of 3 years.…”
Section: Biofilms and Microbial Matsmentioning
confidence: 99%
“…Las Hoyas is a well-known exceptional upper Barremian deposit made famous by the discovery of articulated and soft-bodied animals with preserved soft- tissues 13 . This soft-tissue preservation is linked to the presence of microbial mats, which would have played a crucial role in maintaining the integrity of the organism bodies and the biological rests therein produced 14 16 . According to the palaeogeographic, sedimentological, and palaeontological data, this Barremian locality was an inland freshwater ecosystem with subtropical seasonality and no marine influence 17 – 19 .…”
Section: Introductionmentioning
confidence: 99%